FRANCOLITTERA: Pengembangan Media Interaktif Berbasis Web untuk Pembelajaran Littérature Française - Athoriq, Ardhan Bintang Arasy; Sunendar, Dadang; Mulyadi, Yadi (Faculty of Languages and Arts, Universitas Negeri Padang, 2026)
French literature education in Indonesian universities currently faces significant obstacles due to dependence on passive media (87.7%) and high linguistic barriers (77.2%) that make it difficult for students to understand the syntax and meaning of complex literary texts. This study aims to develop and test the feasibility of Francolittera, a web-based interactive learning medium designed to address these gaps. Using the Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), this study involved 57 students in the needs analysis stage and 25 students in a limited operational trial. The evaluation instrument was developed by adapting the Learning Object Review Instrument (LORI) 2.0 framework. The result of the development is a web platform with a hierarchical material structure (period, author, work) that integrates asynchronous reflective review features with a curation system by administrators to maintain content and interaction quality. Based on the final evaluation on a scale of 1–5, the media was categorized as Very Suitable with an overall average score of 4.38, covering material expert validation (4.50), media expert validation (4.25), and user acceptability testing (4.40). These results indicate that Francolittera has the potential to support independent learning, as reflected in the level of user acceptance of the asynchronous reflective review feature, which facilitates interpretive understanding of literary works in the context of use without direct supervision.